2018
DOI: 10.1103/physreva.97.033816
|View full text |Cite
|
Sign up to set email alerts
|

Achieving a high- Q response in metamaterials by manipulating the toroidal excitations

Abstract: The excitation of toroidal multipoles in metamaterials was investigated for high-Q response at a subwavelength scale. In this paper, we explore the optimization of toroidal excitations in a planar metamaterial comprised of asymmetric split ring resonators (ASRRs). It was found that the scattering power of toroidal dipole can be remarkably strengthened by adjusting the characteristic parameter of ASRRs: asymmetric factor. Interestingly, the improvement in toroidal excitation accompanies increment on the Q-facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 53 publications
0
38
0
Order By: Relevance
“…Fano resonances in metasurfaces, which result in narrow transmission or reflection window, have also got a great deal of attention recently for their wide applications in biosensing, slow light, optical switching, and enhancing nonlinear interactions . The optimization of Q factor and intensity of the Fano resonances plays a key role in the real applications of Fano resonances . Fano resonance with Q factor higher than 10 4 has been experimentally demonstrated in gigahertz (GHz) with a metallic metamaterial .…”
Section: Single‐dimensional Manipulation Of Optical Waves With Metasumentioning
confidence: 99%
“…Fano resonances in metasurfaces, which result in narrow transmission or reflection window, have also got a great deal of attention recently for their wide applications in biosensing, slow light, optical switching, and enhancing nonlinear interactions . The optimization of Q factor and intensity of the Fano resonances plays a key role in the real applications of Fano resonances . Fano resonance with Q factor higher than 10 4 has been experimentally demonstrated in gigahertz (GHz) with a metallic metamaterial .…”
Section: Single‐dimensional Manipulation Of Optical Waves With Metasumentioning
confidence: 99%
“…The multiple wave interference effect and near‐field coupling effect between layers make the few‐layer metasurface a powerful platform to tailor the reflection, transmission, and absorption of electromagnetic waves. By utilizing the multiple wave interference effect between the functional layers, Chen et al proposed a wide‐angle antireflection coating in the terahertz frequency range .…”
Section: Prominent Applications In Few‐layer Metasurfacesmentioning
confidence: 99%
“…[ 38 ] The radiative feature of toroidal geometric is quite unique, resulting from its fantastical field localization configuration in a head‐to‐tail manner. [ 39–41 ] It was found that the toroidal metamaterials could enhance the light‐matter interaction within a small volume, which subsequently produces radiation patterns that couple weakly to the free space. [ 34,35,39–41 ]…”
Section: Introductionmentioning
confidence: 99%